ASPEK HUKUM PERLINDUNGAN DESAIN INDUSTRI KERAJINAN KERANG MUTIARA DALAM PEMBERDAYAAN USAHA KECIL DI KOTA AMBON - Muchtar A. H. Labetubun (SASI, 2011)
Agenda Intellectual Property Rights in particular the actual industrial designs among other things how the autonomous regional government can develop the potential of intellectual property rights owned by the community. Various potential intellectual property rights in the form of knowledge, skills and wisdom of local characteristics such as shellfish Craft Pearls can be protected and utilized for the greater good of society and regions. One potential intellectual property rights in the city of Ambon is the pearl handicraft products, therefore diligence pearl mussels need IPR protection and utilization of industrial design, especially for the greater public interest, especially Maluku Ambon City. Protection of industrial designs pearl handicraft products of the designers have not registered industrial design rights because many of those who do not know the first to file registration system adopted Industrial Design Law No. 31 of 2000, so that n Trademark Copyright protection of intellectual property as an alternative to Craft Shells Of Pearls .